Development of a Severe TBI Consensus-Based Treatment Protocol Conference in Latin America - Hendrickson, Peter (World Neurosurg, 2017)
BACKGROUND: Severe TBI (sTBI) is a significant global health problem disproportionately affecting Low and Middle Income Countries (LMICs). Management of intracranial hypertension in sTBI is crucial to survival and optimal recovery. High Income Country practitioners routinely use Intracranial Pressure (ICP) monitors although their utility has been questioned. ICP monitors are usually unavailable in LMICs. No consensus based/tested protocols or literature exists for sTBI treatment without ICP monitoring. METHODS: Investigators developed serial SurveyMonkey surveys for Latin American neurointensivists and neurosurgeons to determine current practice. These clinicians had extensive, routine, ongoing experience in sTBI without ICP monitoring. Surveys were administered and analyzed before/during/after a 2015 Buenos Aires consensus conference. Investigators identified areas of convergence blinded from colleagues’ responses. A 47 clinician task force, representing 15 countries, who routinely manage sTBI patients without monitors developed consensus-based treatment guidelines during a three-day facilitated conference. RESULTS: Elements were added to the protocol at an 80% agreement threshold. Follow-on surveys resolved remaining elements to 97% agreement. The protocol addresses both tapering (upon improvement) and neuroworsening. Staged treatment options were identified, plus unique clinical practice issues. This process introduced a research method to a large, multi-disciplinary group of LMIC clinicians. This paper describes the process used to develop an LMIC-specific protocol which is transferrable to other diseases/injuries. The protocol is being tested in 5 LMICs. CONCLUSIONS: We derived consensus-based guidelines for sTBI treatment without ICP monitoring, and introduced a research method to a large, multi-disciplinary group of LMIC clinicians naive to such methods.